IMPROVING THE FISHERY BUSINESS PERMIT ISSUANCE USING BUSINESS PROCESS IMPROVEMENT - Friesca Erwan; Fariz Aulia Alzi; Hasan Yudie Sastra; Ilyas Ilyas; Nur Izzaty; Didi Asmadi (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2022)
This study aims to analyse the actual business process applied in the Capital Investment Agency and One-Stop Licensing Centre of Aceh Province, mainly on issuing a fishery business permit. The institution has established 240 working hours (equivalent to 14,400 minutes) to issue the permit based on the SOP (standard operating procedures). However, a field observation showed that the actual process time exceed up to 600 hours (equivalent to 37,104 minutes). To investigate the gap and analyse the business process activities, this study employs Business Process Improvement (BPI) which consists of phase 1: organizing for improvement, phase 2: understanding the process, and phase 3: streamlining. This study occupies Bizagi Modeler to build and simulate a systematic business process model according to Business Process Modelling and Notation (BPMN). Based on the simulation process, the actual business process resulted 110 activities with total time 37,104 minutes, while the redesign model resulted 72 activities with total time 197.25 working hours (equivalent to 11,835 minutes). The redesign model further measured using devil’s quadrangle and obtained 68.11% efficiency. The efficiency aligns with better flexibility and service quality improvement.